Pseudomonas aeruginosa-mediated cr(VI) bioremediation: mechanistic insights and future directions - Mat Arisah, Fatini; Ramli, Norhayati; Ariffin, Hidayah; Toshinari, Maeda; Ahmad Farid, Mohammed Abdillah; Mohd Yusoff, Mohd Zulkhairi (Taylor and Francis, 2024)
Contamination of hexavalent chromium (Cr(VI)) is a major environmental issue since it has the ability to cause cancer and genetic mutations. Bioremediation techniques using Pseudomonas aeruginosa have emerged as potential methods to tackle this problem. This study offers a thorough examination of the underlying mechanisms and potential future paths in the process of P. aeruginosa-mediated Cr(VI) remediation. Herein, the strategies used by P. aeruginosa were examined for the removal of Cr(VI) via processes such as biosorption, intracellular reduction, and extracellular metabolism. In addition, the function of extracellular polymeric substances (EPS) in capturing and isolating Cr(VI) was studied and the possibility of using genetic engineering techniques to improve P. aeruginosa’s ability to remove Cr(VI) from the environment was explored. In addition, we investigate the difficulties related to the use of P. aeruginosa for Cr(VI) bioremediation, such as environmental conditions and the presence of other microorganisms, and suggest potential areas for further study. These include the development of bioremediation strategies using consortia of microorganisms and the incorporation of nanomaterials to improve the removal of Cr(VI). This study seeks to enhance the development of sustainable solutions for remediating Cr(VI) by integrating existing information and identifying future research directions, with a focus on employing P. aeruginosa.